Collaborative learning and co-author students in online higher education: a-REAeduca – collaborative learning and co-authors - Nobre, Ana (2018)
The technologies themselves cannot be analyzed as instruments per se, nor can they be exhausted in their relation with science. There is a social and even an individual dimension that affects our own way of relating to society. It is in open education that we have been developing our educational practices. This chapter presents a collaborative learning activity, the curricular unit Materiais e Recursos para eLearning, part of an on-line Master in Pedagogy of eLearning, Universidade Aberta, Portugal. In the present work, the authors dedicate their attention to co-learning and co-research, as processes that help to exemplify some situations, the a-REAeduca. The data collection was supported essentially by the content analysis technique.